Cidades em ruínas: a história a contrapelo em Inferno Provisório, de Luiz Ruffato - Giovanna Dealtry (Estudos de Literatura Brasileira Contemporânea)
In an era dominated by terms such as "localism" and "globalization", which show the importance contemporaneity gives to space, would it still be worthy to dedicate on eself to a body of work that aims to pursue the last fifty years of Brazilian history from a perspective that, initially, seems to favor focusing one's gaze precisely on modernity's time paradigms? This is one of the questions that this article on the literary project Inferno provisório, by LuizRuffato, seeks to answer. In considering Walter Benjamin's ideas on the concept of history, Iinvestigate the path taken by Rufatto in his quest to understand Brazil from the point of view of the proletariat without, however, abdicating from fictional innovation.